Strategi Pemilihan Lokasi Usaha Yang Optimal Dan Strategis Untuk Keberhasilan Bisnis Bagi Para Perintis Usaha - Desy Rosiana; Rusnandari Retno Cahyani (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
Business location is very important because it can influence the success or failure of the business. Factors such as accessibility, target market, competition, infrastructure, costs of renting or purchasing property, and local regulations are considerations in choosing the right business location, so entrepreneurs need to make careful considerations regarding choosing a strategic business location. In this era, building a business or determining a business location is not an easy thing, because the business location is very important for the sustainability of the company. If this is not the case, the company will experience a very fatal failure and could even go bankrupt. Determining a business location also requires quite a lot of costs, there are many unexpected costs and it could actually increase expenses for the entrepreneur and not get a profit from choosing the business location. The aim of this research is to find out the influence of choosing a business location on business success and success. Researchers conducted this research using research methods by means of literature reviews. Data collection was carried out by searching and collecting several articles from the internet, previous research journals that were relevant to the discussion of this research, reading books related to the title of this research, and many more. It would be a good idea for researchers to also expand their research to various companies in order to gain broader insight into choosing a good and correct business location for the success and success of the company they are building. Not only that, the researcher also got the most valid source of information because the researcher interviewed directly the relevant parties who understand how to manage and choose a good and correct business location.